Analysis of the Use and Acceptance of Government Social Media in the South Sumatra Community Using the UTAUT 2 Method (Case Study : Instagram of the South Sumatra Provincial Food Crop and Horticulture Agriculture Office @pertaniantph.sumsel) - Falah, Miftahul; Wedhasmara, Ari; Putri, Amelia Rizki; Tania, Ken Ditha; Ibrahim, Ali; Sevtiyuni, Putri Eka (Generic, 2025)
The widespread accessibility of the internet via smartphones, laptops, and tablets, along with the convenience of carrying these devices anywhere, has transformed social media from merely a communication tool into a key source of information. Instagram, in particular, focuses on visual aesthetics. Many government agencies in Indonesia now have Instagram accounts to engage with the public, as social media-especially Instagram-is increasingly viewed as a popular platform for information dissemination across various demographic groups. One such agency is the South Sumatra Provincial Food Crop and Horticulture Agriculture, which operates under the Instagram handle @pertaniantph.sumsel. However, engagement with their Instagram community remains low, as seen from the limited number of likes and comments on their posts. To investigate the factors contributing to this issue, a study was conducted using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model, gathering data from 516 questionnaire respondents who follow the @pertaniantph.sumsel account. The data was analyzed using SmartPLS, revealing that Behavioral Intention significantly impacts Usage Behavior, Effort Expectancy significantly affects Behavioral Intention, Facilitating Conditions influence Usage Behavior, Habit has a significant impact on Behavioral Intention, Hedonic Motivation affects Behavioral Intention, and Social Influence also plays a key role in shaping Behavioral Intention.